MENINGKATKAN HASIL BELAJAR MELALUI MEDIA CANVA DALAM PEMBELAJARAN IPA MATERI PENYESUAIAN DIRI MAKHLUK HIDUP TERHADAP LINGKUNGANNYA PADA SISWA KELAS V SD NEGERI 08 KOTA TERNATE - Marasabessy, Apridayani (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
In this study, Canva media was used to improve student learning outcomes, especially in SD Negeri 8 Ternate City. This study used the PTK method with the aim of the study to determine/understand the use of Canva media in improving the ability of science learning outcomes of students at SD Negeri 8 Ternate City. The results obtained from this study The use of Canva media can improve student learning activities, seen from the average student learning activity in Cycle I of 63.25% and in cycle II of 77%, experiencing an average increase of 13.75%, with a Good predicate. Therefore, the use of Canva media can improve the learning outcomes of science subjects in grade V of SD Negeri 8 Ternate City, this is evidenced by the percentage of test results in cycle I and cycle II obtained based on written tests on students in the form of essay questions totaling 10 questions. In cycle I with a completeness result of 43.75% then experienced an increase in completeness of 81.25% in cycle II.